Impacts of Thermal Inertia Factor on Adiabatic Decomposition of 40% Mass Content DCP in Ethyl Benzene - Xiaojuan Wu; Liping Chen; Guoning Rao; Wanghua Chen; Ruili Yin (Journal of Chemistry)
To reduce the fire and explosion accident of dicumyl peroxide (DCP) in experiment and production, the thermal hazards of DCP and 40% mass content DCP in ethyl benzene (40% DCP) have been studied by the differential scanning calorimeter (DSC) and the accelerating rate calorimeter (ARC) in this paper. DSC experiment showed that ethyl benzene has no effect on the characteristic parameters of thermal decomposition of DCP, such as the temperature of the exothermic peak (Tpeak) and the decomposition energy (Ea), and the thermal decomposition reaction of 40% DCP followed the one-step reaction principle. ARC experiment showed that with the increase of inertia factor (Φ), the measured initial decomposition temperature (Ton) would be higher and the caculated Ea and pre-exponential factor (A) would be greater. It was also proved that after modification of Φ, TD24 was relatively consistent near Ton, but different at higher temperatures. Fisher's correction method was used to verify the necessity of consistency between experimental conditions and prediction conditions.